ANALYSIS OF ECONOMIC GROWTH, HDI, AND POPULATION IMPACT ON POVERTY IN PAPUA (2012-2017) - Ira Febrianty Yosmaliza; Agustinus Suryantoro (Journal of Applied Economics in Developing Countries, 2022)
This research aims to analyze the specific effects of economic growth, the Human Development Index (HDI), and population size on poverty levels in Papua Province from 2012 to 2017. Secondary data is used by this research from the Central Bureau of Statistics. The analysis used in this research is analysis of panel data consisting of cross sections of 29 districts/cities and time series data over the period 2012-2017. The model of data panel uses is fixed effect model. The results of the research showed that HDI and population rates affect negatively and significantly on poverty in Papua during 2012-2017. Meanwhile, the economic growth rate variable affects poverty negatively and not significantly in Papua during 2012-2017. The high coefficient of determination (R2 = 0.973966) indicates that 97.4% of the variation in poverty levels in Papua Province can be explained by the combined effects of economic growth, HDI, and population size. This finding underscores the significant role of human development and population management in poverty alleviation efforts. Future policies should prioritize education, healthcare, and sustainable population growth to effectively reduce poverty in the region.